2016
DOI: 10.1177/1468017316654343
|View full text |Cite
|
Sign up to set email alerts
|

The impact of personal budgets on unpaid carers of older people

Abstract: Summary: This paper focuses on the impact of a personal budget (PB) -either in the form of a direct payment (DP) or managed personal budget (MPB) -on the role of unpaid carers of older budget holders. Data were collected via postal survey of 1500 unpaid carers and semistructured interviews with 31 carers. However, carers supporting DP users did experience higher levels of stress. This seemed linked to the additional responsibilities involved in administering the DP. Carers seemed relatively unsupported by thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
(37 reference statements)
2
13
0
Order By: Relevance
“…Previous research has noted that ‘third-party organisations’ support improves outcomes for individuals with and without unpaid care [ 30 , 86 ]. Backed by qualitative research it has been widely accepted that DP support is critical to take-up of DPs [ 87 ], that absence of payroll support can put people off using DPs [ 38 ] and that DP support can ease the burden felt by unpaid carers [ 36 , 88 ] but the lack of a clear association between the role of support services and particularly support for recruiting care (as demonstrated in this study), has weakened the priority given to DP support.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has noted that ‘third-party organisations’ support improves outcomes for individuals with and without unpaid care [ 30 , 86 ]. Backed by qualitative research it has been widely accepted that DP support is critical to take-up of DPs [ 87 ], that absence of payroll support can put people off using DPs [ 38 ] and that DP support can ease the burden felt by unpaid carers [ 36 , 88 ] but the lack of a clear association between the role of support services and particularly support for recruiting care (as demonstrated in this study), has weakened the priority given to DP support.…”
Section: Resultsmentioning
confidence: 99%
“…Attempting to address these issues, Woolham et al [ 36 ] compared the outcomes of DPs to managed budgets (MBs) among older people. Their findings suggest no significant differences in social care outcomes between the service types, although DP recipients scored higher for process outcomes (timing of care and satisfaction with services).…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence of positive impacts of personal budgets for carers, especially in terms of the flexibility afforded, allowing carers to be able to better balance caregiving with their other responsibilities and make employment decisions (Larkin, 2015; Woolham et al., 2018). Other studies found that personal budgets supported carers to have free time for their own social, leisure or essential activities (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, there were also some negative aspects. Some carers report that managing personal budgets was stressful, even if this somewhat reduced over time (Larkin, 2015; Moran et al., 2012; Woolham et al., 2018). Carers also described that sometimes, they did not have enough confidence in those providing the support to be able to stand back from caregiving and feel less anxious (Larkin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Building upon the principles of greater choice and influence of those who use services, and upon the existing system of Direct Payments (a cash payment to service users to pay for their own care), a proposal for Personal Budgets (a wider form of Direct Payment) for individual service users was developed (Department of Health, 2005), whether managed by the individual or by others, including care managers, on their behalf (Department of Health, 2008a). Subsequent studies have suggested that older people, in particular, placed less value on self-management of resources than others (Glendinning et al 2008;Slasberg et al 2012;Woolham & Benton, 2013;Woolham et al 2017Woolham et al , 2018 and support by a care manager or coordinator, from either public or non-statutory organisations, was viewed as important by older people in managing their care (Woolham et al 2017).…”
Section: Introductionmentioning
confidence: 99%